Multi-charge transfer from photodoped ITO nanocrystals. Issue 23 (18th October 2021) - Ghini, Michele; Rubino, Andrea; Camellini, Andrea; Kriegel, Ilka
Abstract : Photodoped ITO nanocrystals (NCs) enables multi-electron transfer processes unveiled by F4TCNQ titration analysis. Metal oxide NCs are emerging as extremely versatile materials for energy storage and conversion technologies. Abstract : Metal oxide nanocrystals are emerging as an extremely versatile material for addressing many of the current challenging demands of energy-conversion technology. Being able to exploit their full potential is not only an advantage but also a scientific and economic ambition for a more sustainable energy development. In this direction, the photodoping of metal oxide nanocrystals is a very notable process that allows accumulating multiple charge carriers per nanocrystal after light absorption. The reactivity of the photodoped electrons is currently the subject of an intense study. In this context, the possibility to extract efficiently the stored electrons could be beneficial for numerous processes, from photoconversion and sunlight energy storage to photocatalysis and photoelectrochemistry. In this work we provide, via oxidative titration and optical spectroscopy, evidence for multi-electron transfer processes from photodoped Sn : In2 O3 nanocrystals to a widely employed organic electron acceptor (F4TCNQ). The results of this study disclose the potential of photodoped electrons to drive chemical reactions involving more than one electron.